Midwifery Care in Adolescent Dysmenorrhea with Acid Therapeutic Dimadrasah Tsanawiyah Daarun Najah Teratakbuluh 2019: Midwifery Care in Adolescent Dysmenorrhea with Acid Therapeutic Dimadrasah Tsanawiyah Daarun Najah Teratakbuluh 2019 - Een Husanah (Institute Of Computer Science (IOCS), 2020)
Dysmenorrhea is pain in the pelvic area due to menstruation and the production of a prostaglandin. in Indonesia the incidence of dysmenorrhea is composed of 72.89% and 21.11% of primary dysmenorrhea and secondary dysmenorrhea dysmenorrhea incidence ranges from 45-95% among women of childbearing age. The role of the midwife one for primary dysmenorrhea interference problems with their education about menstruation in adolescents dismenore.Minuman turmeric pain-reducing acid on primary dysmenorrhea have minimal side effects and are not adabahaya if taken as a case study kebiasaan.Laporan was created with the purpose to provide care in adolescents who experience dysmenorrhea.The method used is a case study given to the teenager who mengalamiDismenore in MTs Daarun Najah with turmeric acid therapy. After being given the care for 3 times the therapy to patients 2 times a day in the morning and during the day is consumed after a meal, the results obtained are adolescent dysmenorrhea decreased pain numeric scale from number 4 to the scale number 2. Expected results of this case study can provide useful information on adolescent reproductive health and read the posters that have been pasted on the bulletin board at school.